Korean sibling caregivers of individuals diagnosed with schizophrenia - Mijung Park; Kwang-Ja Lee (JMIR Publications, 2017)
Siblings of individuals diagnosed with schizophrenia are an important source of family caregiving. Unfortunately, limited information is available about sibling caregivers because existing studies have focused on other family relationships such as parents, spouses, and children. To fill the knowledge gap, the purpose of this study is to describe Korean sibling caregivers' experience with individuals diagnosed with schizophrenia. Guided by Colaizzi's descriptive phenomenological methodology, we conducted in-depth, semi-structured, face-to-face interviews with eight individuals who have a sibling (1) diagnosed with schizophrenia and (2) hospitalized in an inpatient psychiatric unit. We discerned six key themes: sorrow, burnout, shame, different perspectives in life, acceptance, and responsibility. We categorized these themes into three groups: suffering, hope, and responsibility and obligation. Sibling caregivers of individuals with schizophrenia experience a mixture of several emotions. Participants loved their brother or sister with schizophrenia, but at the same time they felt shame and fear. While they were burdened by the responsibilities of caregiving, they remained loyal to their sibling with schizophrenia, continuing to help their siblings reach their full potential. Although participants were confused about the symptoms of schizophrenia, they were committed to learning more about the illness. Because we conducted the current study in Korea, the findings of this study may be unique to Korea culture. Further studies are needed to compare and contrast nuanced differences in sibling caregivers' experience among different cultural groups.